Donor PNPLA3 rs738409 genotype is a risk factor for graft steatosis. A post-transplant biopsy-based study - Trunečka, Pavel; Míková, Irena; Dlouhá, Dana; Hubáček, Jaroslav A; Honsová, Eva; Kolesár, Libor; Lánská, Věra; Fraňková, Soňa; Šperl, Jan; Jirsa, Milan; Poledne, Rudolf (Digestive and liver disease, 2018)
BACKGROUND & AIMS: The rs738409 c.444C > G (p.I148M) polymorphism in PNPLA3 is a major factor predisposing to non-alcoholic fatty liver disease. The aim of the study was to clarify the impact of liver and extrahepatic expression of the PNPLA3 p.148M variant on liver graft steatosis after liver transplantation. METHODS: Fat content was assessed in liver biopsies from 176 transplant recipients. During a period of 4 ± 1 years after transplantation, 17 patients developed grade 3 steatosis, 14 patients grade 2 steatosis, 56 patients grade 1 steatosis, and 89 patients grade 0 steatosis. The influence of the recipient and donor rs738409 genotype and clinical and laboratory data on liver fat content were analyzed using ordinal logistic regression. RESULTS: The PNPLA3 rs738409 CC/CG/GG genotype frequencies, respectively, were 0.494/0.449/0.057 in the graft donors and 0.545/0.330/0.125 in the graft recipients. In the multivariate analysis, the presence of the PNPLA3 c.444G allele in donor (OR 1.62; 95%CI 1.12-2.33), post-transplant BMI (OR 1.14; 95%CI 1.07-1.22), diabetes mellitus (OR 1.99; 95%CI 1.22-3.22), and serum triglycerides (OR 1.40; 95%CI 1.11-1.76) were independent risk factors for increased liver graft fat content. CONCLUSIONS: These data indicate that the liver expression of the PNPLA3 p.148M variant confers a genetic predisposition to liver graft steatosis along with nutritional status and diabetes.
Keywords: Fatty Liver; játra; Lipase; Membrane Proteins; Triglycerides; Biopsy; Polymorphism, Single Nucleotide; Humans; index tělesné hmotnosti; lidé středního věku; Body Mass Index; Risk Factors; jednonukleotidový polymorfismus; Female; rizikové faktory; dospělí; Tissue Donors; Genotype; lidé; Liver transplantation; alografty; biopsie; Diabetes Mellitus; ztučnělá játra; Adiposity; Liver Transplantation; transplantace jater; Adult; Postoperative Complications; pooperační komplikace; dárci tkání; ženské pohlaví; triglyceridy; Liver; Male; Liver biopsy; Middle Aged; NAFLD; membránové proteiny; Allografts; genotyp; příjemce transplantátu; Transplant Recipients; mužské pohlaví; diabetes mellitus; adipozita; lipasa; PNPLA3